2022
DOI: 10.21203/rs.3.rs-1499191/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding Physical and Cognitive Impacts of PM Concentrations at Ultra-fine Scales

Abstract: The human body is an incredible and complex sensing system. Environmental factors trigger a wide range of automatic neurophysiological responses. Biometric sensors can capture these responses in real time, providing clues to the underlying biophysical mechanisms. Here we show biometric variables can be used to accurately estimate ultra-local particulate matter concentrations in the ambient environment with high fidelity (r$^2$ = 0.91) and that smaller particles are better estimated than larger ones. Inferring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Multiple trials may improve the predictive power of the model, similar to the previous single-subject experiment. 14 Through the usage of SHAP values, it is also revealed that skin temperature and heart rate hold the most importance for this empirical ML model. Research has shown that there is a relationship between skin temperature and heart rate in children, 26 but the short-term effects of PM concentration on physiological responses such as skin temperature and heart rate are still being explored.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Multiple trials may improve the predictive power of the model, similar to the previous single-subject experiment. 14 Through the usage of SHAP values, it is also revealed that skin temperature and heart rate hold the most importance for this empirical ML model. Research has shown that there is a relationship between skin temperature and heart rate in children, 26 but the short-term effects of PM concentration on physiological responses such as skin temperature and heart rate are still being explored.…”
Section: Discussionmentioning
confidence: 96%
“…Empirical ML models that predict PM concentration on multiple participants extend the results that predicted PM concentration from the biometric signature of a single participant. 14 The first model, Figure 6, included all biometric characteristics collected and derived, represented by 324 columns, ranging from EEG frequency spectral densities to pupillometrics to skin temperature and heart rate. This is an improvement over the previous results from a single subject, which had a goodness of fit of r 2 = 0.91 between the predicted and actual PM concentrations for the test data set.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations